Peran Lembaga Amil Zakat Griya Yatim dan Dhuafa dalam Meningkatkan Muzakki di Jebres - Adella Permata Sari; M Fatchurrohman; S Subagyo (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Lembaga Amil Zakat (LAZ) is an institution established by the government and the private sector to manage zakat, starting from collecting zakat to distributing it to people who are entitled to receive zakat or mustahiq. The existence of this institution in fact provides convenience for muzakki in distributing their zakat worship. In the economic and social context, the activities carried out by LAZ are considered capable of assisting the government in overcoming the problem of poverty that occurs. This research was conducted at one of the zakat institutions in Surakarta, namely LAZ Griya Yatim and Dhuafa (GYD) which is active in helping the collection and distribution of zakat in the city. LAZ GYD also has various ways to collect zakat which makes it easier for muzakki to pay zakat. Not only that, LAZ GYD also has various programs for zakat distribution so that it is targeted and effective with priorities on education, economy and social. It is interesting to study the efforts made by LAZ GYD in more depth to see the institution's efforts to increase the number of muzakki, especially in Jebres District, Surakarta. The results show that LAZ GYD conducts outreach activities in collecting zakat personally or using communication media. In addition to providing information, outreach also plays a role in raising awareness and providing education to the wider community. In addition, socialization plays an important role in inviting and raising the awareness of prospective muzakki to tithe through the LAZ GYD programs. Then to increase muzakki's trust, LAZ GYD implements accountable and transparent management. This is also used as an effort to attract prospective muzakki to tithe through the Griya Yatim and Dhuafa Amil Zakat Institution (LAZ GYD).